THE EFFECT OF RESPONSIBILITY, DISCIPLINE, PERFORMANCE, AND EMPLOYEE POLICY ON PARTICIPANT SERVICE SATISFACTION - Sawal Sartono; Mokhamad Eldon; Indra Hadi Rosyid Novela (BEMJ : Business, Entrepreneurship, and Management Journal, 2024)
With the rapid development of health services businesses, more and more public and private hospitals are offering health services. One form of service is providing drugs recommended by doctors. The existence of drug supplies in a hospital is very important because it is the main component in building a quality hospital. The problem formulation is: "How Big is the Influence of Responsibility, Discipline, Performance, and Politeness of Old Age Security Program Employees on Participant Service Satisfaction at BPJS Ketenagakerjaan, Tulungagung Branch Office"? This study aims to determine simultaneously and partially the Influence of the variables of Responsibility, Discipline, Performance, and Politeness of Old Age Security Program Employees on Participant Service Satisfaction at BPJS Ketenagakerjaan, Tulungagung Branch Office. The research method used is quantitative. The subjects of this study were Participants in BPJS Ketenagakerjaan KCP Tulungagung. Data were collected through interviews, observation, and documentation methods. The types of data used are primary and secondary. The results of this study are as follows: There is an influence of responsibility on service satisfaction; There is a positive and significant influence between discipline and service satisfaction. There is a positive and significant influence between performance and service satisfaction. There is a positive and significant influence between politeness and service satisfaction. Responsibility, discipline, performance, and politeness influence service satisfaction.